Jozef Pilsudski : founding father of modern Poland - Zimmerman, Joshua D. (Cambridge, Massachusetts Harvard University Press, 2022)
"An authoritative biography of Jozef Pilsudski, a key figure in interwar Europe regarded as the founding hero of a pluralistic and democratic modern Poland. After the first elected president was assassinated, Pilsudski lost faith in Poles' commitment to democracy, led a military coup, and ruled as a strongman, leaving a complicated legacy"--
Introduction -- Childhood and adolescence -- Exile and romance -- Socialist leader and conspirator -- Into the international arena -- Party leadership and arrest -- An extraordinary escape and a new home in Austrian Galicia -- Creating a party platform -- From a Tokyo mission to the Union of Active Struggle -- Building an armed force for independence -- The Polish legions and the beginnings of World War I -- An emerging national leader -- The father of independent Poland -- Statesman and diplomat -- The state builder -- From the first years of peace to the 1926 coup -- The path to authoritarian rule -- Poland in a changing world -- Pilsudski's last year -- Epliogue -- Pilsudski family trees
Description based on print version record
Includes bibliographical references and index
JSTOR
Keywords: Piłsudski, Józef, -- 1867-1935.; Piłsudski, Józef, -- 1867-1935; Heads of state -- Poland -- Biography; Poland -- History -- 1864-1918.; Poland -- History -- 1918-1945.; Chefs d'État -- Pologne -- Biographies; Pologne -- Histoire -- 1864-1918.; Pologne -- Histoire -- 1918-1945.; BIOGRAPHY & AUTOBIOGRAPHY / Historical; Heads of state; Poland; 1864-1945; Biographies; History